2021
DOI: 10.1002/cncr.33652
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of guideline‐concordant care among young adult women with breast cancer

Abstract: Background Little is known about the real‐world care of young adult (YA) females (aged 20‐39 years) with breast cancer. This study describes factors associated with the receipt of guideline‐concordant care (GCC) among YAs. Methods The authors identified 1259 YA women with invasive breast cancer diagnosed in 2013 in the National Cancer Institute's Patterns of Care study. Hospital records were re‐abstracted, and treatment was verified. Using the National Comprehensive Cancer Network's 2013 breast cancer guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The finding of high compliance with guidelines-recommended treatment in Switzerland mimics the results of a recent study from the United States. The authors analyzed data from 952 YWBC diagnosed in 2013 in the National Cancer Institute’s Patterns of Care Study and found that 81.7% received guideline-concordant care [ 27 ]. This is promising as adherence to treatment guidelines is associated with improved BC outcomes [ 28 ] and shows that physicians are willing to follow evidence-based guidelines for this specific group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of high compliance with guidelines-recommended treatment in Switzerland mimics the results of a recent study from the United States. The authors analyzed data from 952 YWBC diagnosed in 2013 in the National Cancer Institute’s Patterns of Care Study and found that 81.7% received guideline-concordant care [ 27 ]. This is promising as adherence to treatment guidelines is associated with improved BC outcomes [ 28 ] and shows that physicians are willing to follow evidence-based guidelines for this specific group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer and cervical cancer are the third- and fourth-largest malignant diseases that seriously threaten women’s health. Breast cancer and cervical cancer are prone to recurrence and metastasis and seriously affect the physical and mental health of patients ( Buskwofie et al, 2020 ; White et al, 2021 ). The results of the CCK8 assay, colony formation assay, and colony formation assay showed that LEO significantly inhibited MDA-MB-231 or SK-BR-3 cell proliferation at 400–800 μM concentrations.…”
Section: Pharmacodynamics Of Leomentioning
confidence: 99%